Microbial Taxonomy Run Amok. Issue 5 (May 2021) - Sanford, Robert A.; Lloyd, Karen G.; Konstantinidis, Konstantinos T.; Löffler, Frank E.
Abstract : DNA sequencing has led to an explosion in discovery of microbial phylogenetic novelty, especially that represented by uncultivated taxa, to which the traditional system of prokaryotic taxonomy has not adapted. A lack of expansion of the International Code of Nomenclature of Prokaryotes (ICNP, 'the Code') to effectively capture this information has created a 'wild west' situation where names are published or appear in popular reference databases without further verification or validation. The rapid propagation of variant and questionable naming methods has led to widespread confusion and undermines prior accomplishments. We exemplify inconsistencies that have arisen from this practice and endanger the interoperability of scientific findings. The immediate solution to this problem is to develop and adopt universal best practices that are accepted by expert researchers, major publishers, the International Committee on Systematics of Prokaryotes (ICSP), and international microbiological societies. Highlights: Traditional polyphasic taxonomy has been the gold standard for classifying microbes but modern DNA sequencing technology unravels microbial phylogenetic novelty at an unprecedented pace, to which the current framework of nomenclature (the International Code of Nomenclature of Prokaryotes –[the ICNP, 'the Code']) has not yet adapted. Traditional and modern approaches operate in parallel and are often practiced by largely different scientific communities, resulting in redundant, often conflicting, nomenclature. The lack of a unified nomenclature framework, which could be established under a modified Code, has led to a 'wild west' situation in which unvalidated names appear in taxonomic databases and are then adopted by researchers without the effort or background to critique them. The current practice endangers the interoperability of scientific findings because of disagreement between taxonomic databases, inconsistencies with the peer-reviewed literature, proliferation of synonyms resulting from improper naming of taxa, and the naming of taxa with no reference in the literature at all. The global research community is in desperate need of a unified approach, and 'chaos will reign until unity is found'. Potential immediate solutions to the nomenclature quandary include the expansion of the Code to uncultivated and fastidious taxa, often represented only by DNA sequences, and adjustments to the process of publishing proposals for new names and name changes, for example, by creating a new process allowing the research community to critique proposals for new names and/or name changes before names that are included in a Validation List. Database curators should refrain from adopting any proposed new names or new names overwriting existing nomenclature prior to their inclusion in the Validation List published in the International Journal of Systematic and Evolutionary M icrobiology (IJSEM).